David Darby, Structures of Disintegration. Narrative Strategies in Elias Canetti’s Die Blendung - Lépine, François (Études littéraires)

(untitled) (Département des littératures de l'Université Laval, 1993)
Structure of Disintegration. Narrative Strategies in Elias Canetti’s Die Blendung.